The genetic integrity of Labeo capensis and L. umbratus (Cyprinidae) in South Africa in relation to inter-basin water transfer schemes - Ramoejane, Mpho (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2011)
The Orange-Fish and Cookhouse tunnels that are part of a major inter-basin water transfer scheme (IBT) act as a pathway for several fish species from the Orange River system to enter the Great Fish and Sundays River systems in South Africa. These include Labeo capensis and L. umbratus. Labeo capensis was restricted to the Orange River system before the inter-basin water transfer scheme. Labeo umbratus occurred naturally in the Orange River and in southern flowing river systems. Previous studies showed that the two species hybridise in Hardap Dam, located in a tributary of the Orange River system in Namibia. There are also unconfirmed reports of hybrids from Darlington Dam on the Sundays River system. The aim of the thesis was to confirm hybridisation in Hardap Dam, assess whether hybridisation between L. capensis and L. umbratus has occurred in Darlington Dam and to gain a better understanding of the diversity of these two species. Morphology (morphometrics and meristics), a nuclear S7 intron and the mitochondrial cytochrome â™ gene were used to assess for hybridisation. A total of 275 specimens were analysed from across the geographical range of the two species. The two species could be distinguished using morphometrics (dorsal fin base, interorbital width and operculum to eye distance) and meristics (lateral line, origin of the dorsal fin to lateral line, origin of the pelvic fin to lateral line and caudal peduncle scale counts) characters. Hybrids from Hardap and Darlington dams were placed between the two species clusters. Labeo umbratus from the Orange River and southern flowing rivers formed a single cluster. The two species could also be distinguished from each other with six nuclear DNA mutations and hybrids were heterozygous at such sites in both dams. Labeo umbratus populations from the Orange River and southern flowing rivers (Gouritz, Gamtoos, Sundays, Bushmans, Great Fish and Nahoon) formed a single lineage. Analysis of mitochondrial DNA, however, revealed that L. umbratus populations from the Orange River and southern flowing rivers were two lineages that differ from each other by 5 mutations. Labeo capensis could be differentiated from both these lineages. Being maternally inherited, mitochondrial DNA did not reveal hybridisation, but ten specimens with L. capensis haplotypes were found in the Darlington Dam. In Hardap Dam, however, it appears that only L. capensis mitochondrial DNA haplotypes persist, despite morphological and nuclear DNA analysis suggesting that both morphs and hybrids of the two species occur. The genetic integrity of these Labeo species has therefore been compromised in at least Hardap and Darlington dams. The Great Fish and Sundays populations are considered to be under threat of complete introgression. The Kat River and Slagboom Dam populations that were isolated before the IBTs have to remain isolated to protect the genetic integrity of the southern lineage of L. umbratus in these two systems.
Keywords: Cyprinidae -- South Africa -- Darlington Dam; Cyprinidae -- Namibia -- Hardap Dam; Labeo -- South Africa -- Darlington Dam; Labeo -- Namibia -- Hardap Dam; Fishes -- Hybridisation -- South Africa -- Darlington Dam; Fishes -- Hybridisation -- Namibia -- Hardap Dam; Fishes -- Anatomy -- South Africa -- Darlington Dam; Fishes -- Anatomy -- Namibia -- Hardap Dam; Water transfer -- South Africa-- Darlington Dam; Water transfer -- Namibia -- Hardap Dam